DETERMINAN PERTUMBUHAN KREDIT MODAL KERJA PERBANKAN di INDONESIA - Widyawati, Sasanti; Wahyudi, Setyo Tri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This research aims to find out the effect of working capital loan interest rates, non performing loans, third party funds growth and inflation on working capital loans growth. Analysis of data using Error Correction Model (ECM) Domowitz - El Badawi. Using this method, it can be analyzed the impact of short-term and long-term between dependent variable and independent variable with analytical techniques for correcting speed of adjustment in the short-term. The results of this research, in the short term only non performing loans are significant negative effect on the working capital loans growth. For long-term relationship, working capital loan interest rates have a significant negative effect , third party funds growth have a significant positive effect and inflation have a significant negative effect.Keyword: Credit Growth, Non Performing Loans, Third Party Funds, Inflation, ECM Domowitz-El Badawi